The Impact of Functional Health Literacy and Acculturation on the Oral Health Status of Somali Refugees Living in Massachusetts - Paul L. Geltman; Jo Adams; Jennifer Cochran; Gheorghe Doros; Denis Rybin; Michelle Henshaw; Lisa L. Barnes; Michael K. Paasche‐Orlow (2013)
Objectives. We assessed the impact of health literacy and acculturation on oral health status of Somali refugees in Massachusetts. Methods. Between December 2009 and June 2011, we surveyed 439 adult Somalis who had lived in the United States 10 years or less. Assessments included oral examinations with decayed, missing, and filled teeth (DMFT) counts and measurement of spoken English and health literacy. We tested associations with generalized linear regression models. Results. Participants had means of 1.4 decayed, 2.8 missing, and 1.3 filled teeth. Among participants who had been in the United States 0 to 4 years, lower health literacy scores correlated with lower DMFT (rate ratio [RR] = 0.78; P = .016). Among participants who had been in the country 5 to 10 years, lower literacy scores correlated with higher DMFT (RR = 1.37; P = .012). Literacy was not significantly associated with decayed teeth. Lower literacy scores correlated marginally with lower risk of periodontal disease (odds ratio = 0.22; P = .047). Conclusions. Worsening oral health of Somali refugees over time may be linked to less access to preventive care and less utilization of beneficial oral hygiene practices.